Nitrate exposure reprograms hepatic amino acid and nutrient sensing pathways prior to exercise: A metabolomic and transcriptomic investigation in zebrafish (Danio rerio) - Keller, Rosa M.; Beaver, Laura M.; Prater, Mary C.; Truong, Lisa; Tanguay, Robyn L.; Stevens, Jan F.; Hord, Norman G. (Frontiers in Molecular Biosciences, 2022)
Nitrate supplementation is a popular ergogenic aid that improves exercise performance by reducing oxygen consumption during exercise. We investigated the effect of nitrate exposure and exercise on metabolic pathways in zebrafish liver. Fish were exposed to sodium nitrate (606.9 mg/L), or control water, for 21 days and analyzed at intervals during an exercise test. We utilized untargeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis and measured gene expression of 24 genes central to energy metabolism and redox signaling. We observed a greater abundance of metabolites involved in endogenous nitric oxide metabolism and amino acid metabolism in nitrate-treated livers at rest, compared to rested controls. In the absence of exercise, nitrate treatment upregulated expression of genes central to nutrient sensing (pgc1a), protein synthesis (mtor) and purine metabolism (pnp5a and ampd1) and downregulated expression of genes involved in mitochondrial fat oxidation (acaca and cpt2). Our data support a role for sub-chronic nitrate treatment in the improvement of exercise performance, in part, by improving NO bioavailability, sparing arginine, and modulating hepatic gluconeogenesis and glycolytic capacity in the liver.